Large eddy simulation for incompressible flows an introduction - Sagaut, Pierre (Scientific computation, 2006)
'Large Eddy Simulation for Incompressible Flows' presents a comprehensive account and a unified view of this young but very rich discipline. LES is the only efficient technique for approaching high Reynolds numbers when simulating industrial, natural or experimental configurations.